Personal Finance Tax Update, 13th Edition - E. Thomas Garman; Raymond Forgue (Cengage Learning, 2020)
Discover the keys to personal financial management with the practical, reader-friendly introduction in Garman/Forgue's market-leading PERSONAL FINANCE TAX UPDATE, 13E. This step-by-step approach teaches you how to save and invest, manage student loans, file taxes, decrease credit card debt and plan a strong financial future. The latest financial information throughout this edition incorporates significant changes to the U.S. income tax system with the ""Tax Cuts and Jobs Act"" of 2018. Memorable scenarios lifted from actual situations depict a variety of financial challenges - showing you the relevance of what you're learning and the importance of following advice from trusted personal finance experts. Many math-based examples also clearly illustrate how to achieve long-term financial goals through investing. Using the latest financial updates and effective learning tools, this edition prepares you for personal financial success now and throughout your lifetime. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.